La correspondance, espace de partage et lieu de repli : l’échange épistolaire entre Gustave Flaubert et Ernest Feydeau - Catherine Thomas-Ripault (Flaubert: Revue Critique et Génétique)
Ernest Feydeau was a close friend of Flaubert, and one of his most assiduous correspondents. Their epistolary exchange is above all the space where common positions and values circulate: each one states a literary connivance with his addressee, and maintains the myth of a perfect complementarity. However, very quickly the roles are distributed within the letters, and a game of influences is set up through which the writers try to assert their originality and use these friendly relations in a strategic way. The correspondence can then appear as a place of withdrawal, where a certain distance is created between the letter writers. This double movement, between the dream of an elective parity and the denunciation of an intractable difference, can paradoxically give place to a true meeting, and foster the right perception of the other in his singularity.